Digital Transformation in Materials Science: A Paradigm Change in Material's Development. Issue 8 (6th January 2021) - Kimmig, Julian; Zechel, Stefan; Schubert, Ulrich S.
Abstract: The ongoing digitalization is rapidly changing and will further revolutionize all parts of life. This statement is currently omnipresent in the media as well as in the scientific community; however, the exact consequences of the proceeding digitalization for the field of materials science in general and the way research will be performed in the future are still unclear. There are first promising examples featuring the potential to change discovery and development approaches toward new materials. Nevertheless, a wide range of open questions have to be solved in order to enable the so‐called digital‐supported material research. The current state‐of‐the‐art, the present and future challenges, as well as the resulting perspectives for materials science are described. Abstract : The ongoing expansion of digitalization approaches influences material research significantly. The complete workflow of the development of novel materials, from synthesis, over characterization, to fabrication will change within the coming years to a more automatic, data‐driven, and robot‐based approach. The current status is summarized and advantages, challenges, and future perspectives discussed.